# How do you solve 49- [ 3+ 10y - 4( y + 2) ] = - 5( 3y - 6) - [ 5( y - 1) - 9y + 21]?

Jul 16, 2018

Arrange the equation

#### Explanation:

$49 - 3 - 10 y + 4 y + 8 = - 15 y + 30 - 5 y + 5 + 9 y - 21$

after getting rid of parantheses:

$49 - 3 + 8 - 30 - 5 + 21 = - 15 y - 5 y + 9 y + 10 y - 4 y$

Now combine numbers on one side and y terms on the other:

$40 = - 24 y + 19 y$

$40 = - 5 y$

$y = - \frac{40}{5} = - 8$

Your answer is $y = - 8$

Jul 16, 2018

$y = - 8$

#### Explanation:

Given: $49 - \left[3 + 10 y - 4 \left(y + 2\right)\right] = - 5 \left(3 y - 6\right) - \left[5 \left(y - 1\right) - 9 y + 21\right]$
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(blue)("Consider "-[3+10y-4(y+2)]

Multiply inside the square brackets by $- 1$

$- 3 - 10 y + 4 \left(y + 2\right)$

$- 3 - 10 y + 4 y + 8$

$- 3 + 8 - 10 y + 4 y$

$\textcolor{w h i t e}{\text{dd")+5 color(white)("dddd}} - 6 y$

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
$\textcolor{b l u e}{\text{Consider } - 5 \left(3 y - 6\right)}$

Multiply everything inside the brackets by $- 5$

$- 15 y + 30$
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
$\textcolor{b l u e}{\text{Consider } - \left[5 \left(y - 1\right) - 9 y + 21\right]}$

Multiply inside the square brackets by $- 1$

$- 5 \left(y - 1\right) + 9 y - 21$

$- 5 y + 5 + 9 y - 21$

$+ 5 - 21 - 5 y + 9 y$

$\textcolor{w h i t e}{\text{d")-16color(white)("dddd}} + 4 y$
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
$\textcolor{b l u e}{\text{Putting it all back together}}$

$49 + 5 - 6 y = - 15 y + 30 - 16 + 4 y$

$54 - 6 y = - 11 y + 14$

$11 y - 6 y = 14 - 54$

$5 y = - 40$

$y = - 8$